Telehealth to Improve Perinatal Care Access. Issue 5 (September 2022) - Stanley, Angela Y.; Wallace, Jerrol B.
Abstract: The United States has the worst maternal mortality rate of peer countries. Since 1935, the maternal mortality risk among Black women has remained three to four times higher than that of White women. Perinatal health care is not available in all areas, which limits the access for certain groups. Many women in the United States live in maternity care deserts with no access to obstetric providers, whereas others live in areas with very limited access. One way to bridge the gap between effective perinatal care and access to care is use of telehealth. Telehealth allows health care providers to communicate directly with patients that cannot physically be seen in a clinic or hospital. Telehealth is endorsed by the American College of Obstetricians and Gynecologists as an alternate mode to deliver prenatal and postpartum services. The potential for telehealth services as part of perinatal care to reduce maternal and neonatal morbidity and mortality by improving access to care is presented. Abstract : Telemedicine and telehealth are expanding, in part due to use during the COVID-19 pandemic. Feasibility, acceptability, and ease of use have been established. Virtual encounters with health care professionals for prenatal and postpartum care may become a routine part of standard care during the childbirth continuum. The evolution and possibilities of telemedicine and telehealth for improving access to perinatal care are presented.